Review of Surface Runoff in Flood Risk Areas of Makassar Citythrough Modified Rational Methods - Subhan, Andi Muhammad; Faisal, Zulvyah; Musa, Ratna (Politeknik Negeri Ujung Pandang, 2019)
The purpose of this research was to determine the surface runoff and the puddle Â in the of flood risk area in Manggala village. Modified Rational Method had been applied to determine runoff discharge. While, flood risk areas were based on the map from National Disaster Management (BPBD Kota Makassar, 2014). Rainfall data of Manggala village wascollected from 2009 to 2018 from three stations, they areBiringRomang, Panakukkang, and TamangapaKassi. Therefore,Â a Thiessen method had been applied to determine the rainfall area.Research results shown that runoff discharge for return period 5 years was185.38 m3/s, with height around 0,50 to 2,00 m.